2020
DOI: 10.1186/s12898-020-00331-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the vegetation type in Google Earth images using a convolutional neural network: a case study for Japanese bamboo forests

Abstract: Background Classifying and mapping vegetation are crucial tasks in environmental science and natural resource management. However, these tasks are difficult because conventional methods such as field surveys are highly labor-intensive. Identification of target objects from visual data using computer techniques is one of the most promising techniques to reduce the costs and labor for vegetation mapping. Although deep learning and convolutional neural networks (CNNs) have become a new solution for image recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…However, it is not an easy task to apply conventional methods because of field surveys (highly labor-intensive). Recently, deep learning and convolutional neural networks CNNs can be applied for the classification and mapping of soil to reduce the costs and labor for vegetation mapping [54]. Crop types have been classified by applying convolutional neural networks (VGG16 and GoogLeNet, which are pretrained) [55].…”
Section: Lithological Mappingmentioning
confidence: 99%
“…However, it is not an easy task to apply conventional methods because of field surveys (highly labor-intensive). Recently, deep learning and convolutional neural networks CNNs can be applied for the classification and mapping of soil to reduce the costs and labor for vegetation mapping [54]. Crop types have been classified by applying convolutional neural networks (VGG16 and GoogLeNet, which are pretrained) [55].…”
Section: Lithological Mappingmentioning
confidence: 99%
“…Recent years have seen deep learning become a viable solution for image recognition and classification, based on the fact that it no longer requires manual feature extraction. [1] Deep learning is a machine learning technique that makes use of algorithms modeled after the function and structure of the human brain. This represents the artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…It is used for learning visual features in different image processing and remote sensing applications. [1][2][3][4][5] In recent years, the research showed that the convolutional neural network is effective for a variety of applications. Because of this, CNN method is used extensively to accomplish many tasks in different academic and industrial fields.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the kappa coefficient value was 0.8, and the overall accuracy was 94.5%. Using the CNN approach through Google Earth images, Watanabe and colleagues described the vegetation categories (Japan Bamboo forest and Non-Bamboo Forest) [11]. Sanyo Onoda, Ide, and Isumi, three separate bamboo forest locations, were used for the analysis.…”
Section: Introductionmentioning
confidence: 99%